2019
DOI: 10.1002/jcb.28892
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and response to therapy in leukemia

Abstract: A variety of epigenetic factors involved in leukemia pathogenesis. Among various epigenetic factors, microRNAs (miRNAs) have emerged as important players, which affect a sequence of cellular and molecular signaling pathways. Leukemia is known as progressive cancer, which is related to many health problems in the world. It has been shown that the destruction of the blood‐forming organs could lead to abnormal effects on the proliferation and development of leukocytes and their precursors. Despite many attempts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…Several miRNAs have been studied for their diagnostic, prognostic or therapeutic potential [ 73 ]. Results of a meta-analysis of miR-155 and its role in overall survival of AML and CLL patients indicate that high miR-155 expression is associated with lower overall survival of patients, making it a promising prognostic biomarker [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been studied for their diagnostic, prognostic or therapeutic potential [ 73 ]. Results of a meta-analysis of miR-155 and its role in overall survival of AML and CLL patients indicate that high miR-155 expression is associated with lower overall survival of patients, making it a promising prognostic biomarker [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that miRNAs can participate in the occurrence and development of tumors as oncogenes or tumor suppressor genes. Recent years have seen an increase in research on the role of miRNA in the pathogenesis of leukemia [7][8][9] . miR-15a/16-1, miR-188, miR-155, miR-29, miR-17-92, and let-7 are the most commonly differentially expressed miRNAs reported in leukemia [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of miR-101 is engaged by breast cancer cells to ensure higher proteasome activity along with higher proliferation rates [ 109 ]. miRNAs—including miR-101 and others—are associated with cancer immunity [ 110 ] and thus discussed as a potential therapeutic target. In this context, miR-101 is also proposed to target Jak2 [ 111 ].…”
Section: The Immunoproteasome: a Proteasomal Variant Linked To The Hematopoietic Systemmentioning
confidence: 99%